2017
DOI: 10.2147/copd.s141798
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and gas exchange effects of inhaled iloprost in patients with COPD and pulmonary hypertension

Abstract: Studies have shown that vasodilators such as iloprost can be useful for treating pulmonary hypertension (PH). However, in patients with COPD, vasodilators may inhibit hypoxic pulmonary vasoconstriction and impair gas exchange. The efficacy and safety of iloprost inhalation was assessed in 67 patients with PH associated with COPD (COPD-PH), diagnosed by right heart catheterization. Of these, 37 patients had severe PH (mean pulmonary arterial pressure [mPAP] >35 mmHg or mPAP 25–35 mmHg with low cardiac index [<2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…In fact, functional respiratory imaging analysis demonstrated that there was a significant association between regional ventilation and regional vasodilation during iNO therapy. While it could be argued that the lack of a familiarisation 6MWD might have overestimated the clinical response to iNO, the physiological rationale was confirmed and the results are in line with that of recent studies investigating the effects of inhaled iloprost in COPD [100].…”
Section: Advances In Exercise Pathophysiologysupporting
confidence: 82%
“…In fact, functional respiratory imaging analysis demonstrated that there was a significant association between regional ventilation and regional vasodilation during iNO therapy. While it could be argued that the lack of a familiarisation 6MWD might have overestimated the clinical response to iNO, the physiological rationale was confirmed and the results are in line with that of recent studies investigating the effects of inhaled iloprost in COPD [100].…”
Section: Advances In Exercise Pathophysiologysupporting
confidence: 82%
“…Inhaled iloprost resulted in improved gas exchange, without any detrimental effects on pulmonary mechanics nor systemic hemodynamics in ARDS and COPD patients with pulmonary hypertension [4,6]. However, in other studies on patients with COPD and pulmonary hypertension, inhaled iloprost not only failed to improve oxygenation and exercise capacity but, in fact, worsened oxygenation in patients with mild to moderate pulmonary hypertension [8,9]. In studies that demonstrated an improvement, the authors assumed that iloprost was delivered predominantly to the well-ventilated areas of the lung, thus preferentially vasodilating those areas and resulting in decreased ventilation/perfusion (V/Q) mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…The non-severe COPD-PH subgroup was defined as patients with an mPAP of 25–35 mm Hg with a normal CI. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%